Search for the production of narrow tb̄ resonances in 1.9fb-1 of pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We present new limits on resonant tb̄ production in pp̄ collisions at s=1.96TeV, using 1.9fb-1 of data recorded with the CDFII detector at the Fermilab Tevatron. We reconstruct a candidate tb̄ mass in events with a lepton, neutrino candidate, and two or three jets, and search for anomalous tb̄ production as modeled by W′→tb̄. We set a new limit on a right-handed W′ with standard model-like coupling, excluding any mass below 800GeV/c2 at 95% C.L. The cross section for any narrow, resonant tb̄ production between 750 and 950GeV/c2 is found to be less than 0.28pb at 95% C.L. We also present an exclusion of the W′ coupling strength versus W′ mass over the range 300-950GeV/c2. © 2009 The American Physical Society.